2018
DOI: 10.1186/s12884-018-1756-7
|View full text |Cite
|
Sign up to set email alerts
|

Do provider birth attitudes influence cesarean delivery rate: a cross-sectional study

Abstract: BackgroundWhen used judiciously, cesarean sections can save lives; but in the United States, prior research indicates that cesarean birth rates have risen beyond the threshold to help women and infants and become a contributor to increased maternal mortality and rising healthcare costs. Healthy People 2020 has set the goal for nulliparous, term, singleton, vertex (NTSV) cesarean birth rate at no more than 23.9% of births. Currently, cesarean rates vary from 6% to 69% in US hospitals, unexplained by clinical or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 25 publications
1
44
1
2
Order By: Relevance
“…This study is consistent with prior work finding that attitudes and beliefs of individual providers are associated with variation in cesarean delivery rates, individual providers have different thresholds to perform cesarean delivery, and cesarean delivery rate variation is not attributable to patient differences . However, physicians and midwives do not practice in an isolated environment and are subject to the cultural norms, expectations, values, and beliefs existent in their hospital, which need to be accounted for to further explain the wide variation in hospital‐level cesarean delivery rates.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study is consistent with prior work finding that attitudes and beliefs of individual providers are associated with variation in cesarean delivery rates, individual providers have different thresholds to perform cesarean delivery, and cesarean delivery rate variation is not attributable to patient differences . However, physicians and midwives do not practice in an isolated environment and are subject to the cultural norms, expectations, values, and beliefs existent in their hospital, which need to be accounted for to further explain the wide variation in hospital‐level cesarean delivery rates.…”
Section: Discussionsupporting
confidence: 88%
“…The sixth scale measures an individual's perceptions about their labor and delivery unit's norms and consists of eight questions created de novo from concepts identified in CMQCC's “Major Factors Influencing the Culture of Care and the Value of Vaginal Birth.” The survey underwent psychometric analysis, including exploratory factor analysis, iterative revisions using focus groups and individual interviews with labor and delivery personnel, and confirmatory factor analysis . The LCS was administered electronically via Survey Monkey (SurveyMonkey, Inc., San Mateo, CA, USA), and individual invitations to complete the survey were sent out by hospital administrators or labor and delivery unit leaders.…”
Section: Methodsmentioning
confidence: 99%
“…However, the observed differences in labor processes and outcomes noted are likely not fully attributable to the care provided by specific perinatal care providers (eg, midwives vs physicians) or care models, but may be influenced by multiple system factors. For example, the presence of midwives in a hospital may shift the institution's unit culture and approach to birth . Alternately, hospitals with a culture favoring vaginal birth may actively recruit and retain midwives.…”
Section: Discussionmentioning
confidence: 99%
“…
This wide institutional variation cannot be explained by maternal risk factors alone. Health care systems factors may be a primary contributor . One less studied factor is how the presence of midwives as members of labor and birth teams affects variation in cesarean utilization across institutions.…”
Section: Introductionmentioning
confidence: 99%
“…12 This model has been used to connect labor and delivery nurses' attitudes with their intention to deliver supportive care to laboring women. 15 Though promising, these scales did not measure collective norms and values perceived by clinicians practicing on labor and delivery, which are another important facet to organizational culture. Klein et al's studies found differences in attitudes by membership within a discipline (obstetrician vs midwife vs nurse).…”
mentioning
confidence: 99%